Out of the periphery : development of coastal chars in Southeastern Bangladesh - Wilde, Koen de. (Dhaka : The University Press, 2000)
On the development of newly accreted land in the southeastern part of Bangladesh.
Includes index.
Keywords: Regional planning -- Bangladesh; Bangladesh -- Economic policy